HAEMOSTASIS SYSTEM DISORDERS IN CYSTIC AND NIDAL LIVER IMPAIRMENT IN CHILDREN AND THEIR PHARMACOTHERAPY OPPORTUNITIES - V.A. Dudarev; I.V. Kirgizov; Sh.R. Dzhabborov; I.A. Shishkin (Педиатрическая фармакология, 2009)
In the event of a cystic and nidal liver impairment, resulting from the dysfunction of hepatocytes, there are certain haemostasis system disturbances. The article analyzes co agulograms of 75 children with cystic and nidal liver impairment in early school age (aged 6–11 year). The article reviews the diagnostic methods for detecting hemostasis disturbances in case of the given pathology and away to duly and adequately enforce the medication correction of these disorders. This method makes the illness forecast more predictable and manageable.Key words: haemostasis, liver, cystic and nidal liver impairment, children.